Pengaruh Persepsi Kegunaan, Persepsi Kemudahan, Kecepatan, Keamanan 75 dan Kerahasiaan Serta Kesiapan Teknologi Informasi Wajib Pajak terhadap Penggunaan e-Filing Bagi Wajib Pajak Orang Pribadi Di Kota Tangerang, Kecamatan Karawaci - Devina, Shelby; Waluyo, Waluyo (Universitas Multimedia Nusantara, 2016)
The objective of this research was to examine the effect of perceived usefulness, perceived ease of use, speed, security and privacy and readiness technology tax payers information to e-Filing usage. The object of this study is the individual tax payers in Tangerang City, Karawaci District. The selection of the sample is determined based on convenience sampling method. Data used in this study was primary data, id est: questionnaires. The respondent in this study were 110. Data analysis technique in this study using multiple linear regression. The result of this study were (1) perceived usefulness have a significant impact towards e-Filing usage; (2) perceived ease of use have a significant impact towards e-Filing usage; (3) speed does not have a significant impact towards e-Filing usage; (4) security and privacy does not have a significant impact towards e-Filing usage; (5) readiness technology tax payers information does not have a significant impact towards e-Filing usage; (6) perceived usefulness, perceived ease of use, speed, security and privacy and readiness technology tax payers information all simultaneously, have a significant impact towards e-Filing usage. Keywords: e-Filing usage, perceived usefulness, perceived ease of use, readiness technology tax payers information, security and privacy.